2010
DOI: 10.7784/rbtur.v4i2.160
|View full text |Cite
|
Sign up to set email alerts
|

Turismo No Município De Bento Gonçalves (Rs): Análise Do Desenvolvimento De Um Destino Indutor No Brasil

Abstract: Resumo: o objetivo deste artigo é analisar o desenvolvimento turístico do município de Bento Gonçalves (RS), por meio de indicadores de desenvolvimento do setor. Para identificação de indicadores do desenvolvimento, aplicou-se instrumento com questões fechadas e relacionadas aos elementos de duas dimensões do turismo: desenvolvimento socioeconômico e gestão organizacional. Além da aplicação do instrumento, por meio de entrevistas junto a entidades e instituições do setor público e do setor privado no município… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Also, as conclusions, there is that the municipality still faces challenges to improve its infrastructure and its tourism offer. However, the development of tourist activity in the region was expressive, if compared to the research results of Tomazzoni, Possamai, and Lovatel (2010). The destination has attracted demands, whose expenses drive the local economy, generating job and income opportunities for the population, as well as for the activity's external operators.…”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, as conclusions, there is that the municipality still faces challenges to improve its infrastructure and its tourism offer. However, the development of tourist activity in the region was expressive, if compared to the research results of Tomazzoni, Possamai, and Lovatel (2010). The destination has attracted demands, whose expenses drive the local economy, generating job and income opportunities for the population, as well as for the activity's external operators.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Among the main challenges to be overcome, in that research, the following were observed: the insufficiency of municipal resources destined to the tourism portfolio, the lack of planning and a marketing plan for tourism, the low qualification of professionals who worked in the service and the population's lack of knowledge about the importance of tourist activity for the municipality (Tomazzoni et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Na revisão da literatura também foram identificados estudos referentes ao marketing turístico no Brasil. Tomazzoni et al (2010) analisaram o turismo na cidade de Bento Gonçalves. Os autores revelam que a cidade é um dos 65 destinos brasileiros que mais atraem turistas no país.…”
Section: Marketing Turísticounclassified
“…Como justificativa prática, a presente pesquisa torna-se relevante na perspectiva de que os gestores envolvidos neste setor poderão utilizar as informações disponibilizadas para criarem personalidades favoráveis da marca de seus destinos. Suprindo assim as expectativas dos seus clientes e favorecendo o marketing "boca a boca", o que consequentemente atrairá novos turistas e concederá vantagens competitivas (Llodrà-Riera, Martínez-Ruiz, Jimenez-Zarco, Izquierdo-Yusta, & Santana, 2015;Tomazzoni, Possamai, & Lovatel, 2010).…”
Section: Introductionunclassified
“…A cultura da imigração italiana, o cultivo da uva, e indústria vitivinícola que referencia a memória cultural e desenvolve valor de atratividade na região. Assim, elabora o apelo turístico com esses valores de identidade local formando na área como destino indutor e assim: "(...)têm a responsabilidade de propagar o desenvolvimento nos roteiros dos quais fazem parte e, consequentemente, nas regiões turísticas que perpassam" (Tomazzoni;Possamai;Lovatel, 2010, p. 17).…”
Section: Os Roteiros Da Serra Gaúchaunclassified